Analisis Peramalan Harga Daging Ayam Broiler di Pasar Tradisional Provinsi Jambi - Nurhabibah Nurhabibah; Firmansyah Firmansyah; Bagus Pramushinto; Fachroerrozi Hoesni (Universitas Batanghari, 2022)
This study aims to determine the volatility of broiler chicken meat prices in the modern market in Jambi Province and to compile a proper forecasting model for the price of broiler chicken meat in the modern market in Jambi Province. Broiler Chicken Meat Price Forecasting Analysis in Jambi Province uses skunder data which is weekly time series data with the period 2018 - 2021 (September). The data analyzed in this study is the price of broiler chicken meat in the modern market of Jambi Province. The analysis method used to determine the volatility and proper forecasting model for broiler chicken meat prices in the modern market of Jambi Province uses the ARCH/GARCH, ARIMA model. The study concluded that there is volatility in the price of broiler chicken meat in the modern market of Jambi Province. The volatility of broiler chicken meat prices in the modern market is with the ARCH(1) model. n addition, volatility in the modern market of Jambi Province can be seen based on CSD or conditional standard deviations and its volatility value. in the modern market it is 0.01630950. The right forecasting model to determine the price of broiler chicken meat in modern market of Jambi City is to use the ARIMA model.